"I'm Just So Glad That I Saved My Life": A Grounded Theory Analysis of Transgender and Non-Binary Latinx People Navigating Family Rejection and Intergenerational Violence. Issue 5 (6th October 2022) - Gamio Cuervo, Álvaro; Herrawi, Farahdeba; Horne, Sharon G.; Wilkins-Yel, Kerrie G.
Abstract: The purpose of this study was to explore the experience of family rejection on transgender and non-binary Latinx individuals. Related to experiences of rejection, participants were asked about family dynamics and cultural aspects. Data from 12 interviews with Latinx non-binary and transgender adult children were analyzed through a critical-constructivist grounded theory method resulting in a hierarchy comprised of 4 clusters with one core category capturing diverse aspects of the experience of rejection. Deciding how to navigate one's family relationships after experiencing rejection brings forth a difficult decision to save one's life and preserve safety, while torn between expectations to adhere to traditional cultural and familial roles the family has followed to ensure survival. These clusters included: precursors to rejection setting the stage for conformity; ritualization of rejection solidifying otherness and increasing precarity; cultural maintenance of anti-trans rejection within families through reciprocal rejection; and children renegotiating familial expectations to prioritize safety. Two contributions to clinical work and research are offered: (1) rejection is conceptualized as a manifestation of cumulative trauma; (2) contextualizing cultural values within individual and familial environments is essential to understand and prevent family rejection.